3 - The Potential Contribution of Love-Sex Songs to the Spread or Prevention of HIV/AIDS: The Case of the Oromo of Ethiopia - Kelbessa, Workineh (Africa Development, 2021)
This article examines the potential contribution of Oromo love-sex songs to the spread or prevention of the HIV/AIDS. It also shows how Oromo love songs express Oromo beliefs, sexual values, customs, meanings and interpretations of masculinity. The Oromo recite various songs to praise love/sex and lovers; they express, in a manner as explicit as the so-called modern songs, the joy of loving, being loved and the natural energies of lovely sex. They transmit critical information about the Oromo world view by reflecting the beliefs and the values enshrined in Oromo social institutions. This study reveals that Oromo love-sex songs can encourage or discourage risky sexual behaviour. It explains how some Oromo love songs when misunderstood, can influence people to engage in unsafe sex which can potentially spread the HIV/AIDS. Although Oromo sexual ethics are being challenged by external forces, there are some love songs that can educate young people to practise safe sex. Love songs thus can help people to determine real love/lovely sex and negotiate their understanding of sex and HIV/AIDS. This article suggests that Oromo love-sex songs should be critically re-examined to determine to what degree they put ives at risk, and reflect values concerning sexuality, love and gender relations.